Green growth : managing the transition to a sustainable economy learning by doing in East Asia and Europe - Sarkis, Joseph; Vazquez-Brust, Diego A. (Greening of Industry Networks Studies, 2012)
Some call it the 'perfect storm': a devastating combination of financial collapse and environmental catastrophe. A growing consensus recognises the need to shift economies and social structures towards more sustainable models: the very focus of this book. The rising tide of political interest in combining 'growth' with 'green' is now an explicit item on the agenda of key countries, particularly in East Asia and the European Union, where flagship green-growth strategies are at the heart of its blueprint for competitiveness. This volume is a practical guide that helps the reader build a quick, evidence-based understanding of green-growth strategies and challenges. Its cogent analysis of real-life case studies enables policy makers and company executives identify successful strategies they can adopt, and pitfalls they can avoid, in drafting and implementing green growth policies. The contributors' empirical assessment of these studies identifies the structural conditions required for economic growth to be compatible with environmental sustainability and how the transition to a new economic paradigm should be managed. A crucial addition to the debate now beginning in earnest around the world, this volume attempts to understand how we can nurture a new-born model of sustainable growth and help it evolve to maturity.